2017
DOI: 10.15201/hungeobull.66.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Review of soil tillage history and new challenges in Hungary

Abstract: This study provides an overview of the development of soil tillage in Hungary. The primary goal is to present factors that have been promoting and hindering progress in tillage from the first authoritative records -from the eleventh century -up to now when soil tillage became a tool in the climate damage mitigation methods. Progress was restricted during the first eight hundred years of the history of tillage by lack of expertise and the use of primitive tools. In retrospect, much of the traditions are regarde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
1
8
0
4
Order By: Relevance
“…Since the experiment was set on the physically degraded soil [24], the use of soil conservation tillage was expected to improve crumb formation. Birkás et al [25] stated that the reduction of the crumbs in wet season is lower than in the dry season, but the chance of improvement is fairly moderate during average season. This assumption is harmonised to the findings of Gyuricza et al [15], who found poor crumb formation in a Chernozem soil when the dry season replaced a rainy period.…”
Section: Crop Residuesmentioning
confidence: 99%
“…Since the experiment was set on the physically degraded soil [24], the use of soil conservation tillage was expected to improve crumb formation. Birkás et al [25] stated that the reduction of the crumbs in wet season is lower than in the dry season, but the chance of improvement is fairly moderate during average season. This assumption is harmonised to the findings of Gyuricza et al [15], who found poor crumb formation in a Chernozem soil when the dry season replaced a rainy period.…”
Section: Crop Residuesmentioning
confidence: 99%
“…In the physical approach, tillage was believed to play an important role in controlling soil processes. Consequently, the period of several centuries dominated by this approach is referred to as the era of crop-oriented tillage (Birkás et al, 2017). The overestimation of the importance of crop requirements resulted in damaging the soils, which inevitably led to turn to the soil-focused tillage.…”
Section: Discussionmentioning
confidence: 99%
“…The sources of historic and contemporary literature demonstrate that tillage is subject to evolutionary changes along with the civilization development and scientific, technical, and technological progress [7,8]. The contemporary tillage methods and systems are adjusted to the habitat, social and economic conditions, and the agricultural policy in various regions of the world [9][10][11].…”
Section: Introductionmentioning
confidence: 99%